Climate change and tree cover loss affect the habitat suitability of Cedrela angustifolia evaluating climate vulnerability and conservation in Andean montane forests - Ames Martínez, Fressia N. (2025)
Background. Because of illegal logging, habitat fragmentation, and high value timber Andean montane forest Cedrela species (such as Cedrela angustifolia), is endangered in Central and South America. Studying the effects of climate change and tree cover loss on the distribution of C. angustifolia will help us to understand the climatic and ecological sensitivity of this species and suggest conservation and restoration strategies. Methods. Using ecological niche modeling with two algorithms (maximum entropy (MaxEnt) and Random Forest) under the ecological niche conservatism approach, we generated 16,920 models with different combinations of variables and parameters. We identified suitable areas for C. angustifolia trees under present and future climate scenarios (2040, 2070, and 2100 with SSP 3-7.0 and SSP 5-8.5), tree cover loss, and variables linked to soil and topography. Results. Our results demonstrated 10 environmental variables with high percentage contributions and permutation importance; for example, precipitation seasonality exhibited the highest contribution to the current and future distribution of Cedrela angustifolia. The potential present distribution was estimated as 13,080 km2 with tree cover loss and 16,148.5 km2 without tree cover loss. From 2040 to 2100 the species distribution will decrease (from 22.16% to 36.88% with tree cover loss variation). The results indicated that Bolivia displayed higher habitat suitability than Ecuador, Peru, and Argentina. Finally, we recommend developing conservation management strategies that consider both protected and unprotected areas as well as the impact of land-use changes to improve the persistence of C. angustifolia in the future.